(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2022)
In this work there has been studied the rod system operation dependence on the action of external force eﬀects. The system presents a multi-span continuous beam with elastic yielding supports. To identify the stress-strain state of the object under study, a precise analytical method of forces is used. The method of ﬁve moments is used as the resolving (canonical) equations. The ﬁnal results are the parameters of the stress-strain state for a ﬁve-span continuous beam with variable compliance coeﬃcients on 5 intermediate supports and an absolutely rigid left extreme support, deﬂections, bending moments, shear forces, and support reactions.Theoretical provisions and practical results can be used in the design of load-bearing beam structures in buildings and various engineering structures.